2000
DOI: 10.1089/thy.2000.10.595
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Propylthiouracil is Associated with Appearance of Antineutrophil Cytoplasmic Antibodies in Some Patients with Graves' Disease

Abstract: The use of propylthiouracil (PTU) for the treatment of Graves' disease is associated with few adverse effects such as skin eruptions, liver dysfunction, and agranulocytosis. Furthermore, recent studies described the development of antineutrophil cytoplasmic antibody (ANCA)-related glomerulonephritis and vasculitis in patients treated with PTU. Here we investigated whether PTU therapy per se is associated with the appearance of ANCA in patients with Graves' disease. We analyzed 119 serum samples from 117 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
2
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 15 publications
6
66
2
4
Order By: Relevance
“…Although ANCA are present relatively often in patients treated with antithyroid drugs, the prevalence of AAV is much lower (22,(27)(28)(29). In our study, 7 of 11 patients treated with antithyroid drugs who were positive for MPO, PR3, or HLE ANCA did not have, or develop, vasculitis (64%).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Although ANCA are present relatively often in patients treated with antithyroid drugs, the prevalence of AAV is much lower (22,(27)(28)(29). In our study, 7 of 11 patients treated with antithyroid drugs who were positive for MPO, PR3, or HLE ANCA did not have, or develop, vasculitis (64%).…”
Section: Discussioncontrasting
confidence: 50%
“…Clinical signs were present in 2 of 6 ANCA-positive 110 Slot et al patients who had used PTU, in 2 patients using other antithyroid drugs, and in none of the patients who were not treated with antithyroid drugs. The presence of ANCA, and of ANCA-associated vasculitis, in patients using antithyroid drugs for treatment of hyperthyroidism have been recurrently reported (15)(16)(17)(18)(19)(20)(21)(22)(23)27). Reported prevalence of ANCA in patients treated with antithyroid drugs varies from 4% to 46%; prevalence of AAV is lower (0 -1.4%) (22,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…A prevalência de ANCA-MPO nos usuários de drogas antitireoidianas varia de 25-60% nos pacientes tratados com PTU, e de 3,4% nos tratados com metimazol (29)(30)(31). Em uma análise, Sato e cols.…”
Section: Auto-imunidade Anca Por Propiltiouracilunclassified
“…O ANCA-p teve uma correlação significativa com o anticorpo antitireoglobulina e não houve correlação com o anticorpo anti-tireoperoxidase, sugerindo que a severidade da Doença de Graves pode ser um fator responsável para positividade do ANCA-p (1). A proporção de pacientes positivos para este anticorpo aumenta com a duração da terapia, porém não há correlação com idade ou sexo (29). Da mesma forma, não foi relatado aumento da prevalência do ANCA em pacientes com tireoidite de Hashimoto (30).…”
Section: Auto-imunidade Anca Por Propiltiouracilunclassified
“…Despite all medical therapeutic interventions, the patient could not be saved and died due to nosocomial pneumonia and septic shock. www.medicinescience.org | Med-Science 651 more than 18 months has been reported to be associated with the development of ANCA [12,15,16]. Some studies have even reported an increase in ANCA positivity with longer duration of PTU use [17].…”
Section: Introductionmentioning
confidence: 99%